2015
DOI: 10.4081/cp.2015.717
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Gastritis, a Presequeale to Coronary Plaque

Abstract: Helicobacter pylori are considered the most common human pathogen colonizing gastric mucosa. Gastritis with or without H. pylori infection is associated with increase in levels of homocysteine and high-sensitivity C-reactive protein (hs-CRP) but a more pronounced increase is noted in gastritis with H. pylori infection. Increasing level of homocysteine, due to decreased absorption of vitamin B12 and folic acid, together with increased CRP levels in gastritis with H. pylori infection may be the earliest event in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…We determined in our study population with chronic gastritis that the mean of hs-CRP was 1.9±1.6 mg/dl for males and 2.2±1.9 mg/dl for females, which was higher 1 mg/dl than the normal hs-CRP level 9 . Consistent with to the studies in literature, it is found increased hs-CRP levels in parallel to the severity of HP gastritis compared to gastritis without HP infection in our study 6 , 12 . In adition, we also found that serum hs-CRP level of chronic gastritis patients with HP infection was significantly higher than those without HP infection and there was significant association between severity of HP infection and hs-CRP level.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We determined in our study population with chronic gastritis that the mean of hs-CRP was 1.9±1.6 mg/dl for males and 2.2±1.9 mg/dl for females, which was higher 1 mg/dl than the normal hs-CRP level 9 . Consistent with to the studies in literature, it is found increased hs-CRP levels in parallel to the severity of HP gastritis compared to gastritis without HP infection in our study 6 , 12 . In adition, we also found that serum hs-CRP level of chronic gastritis patients with HP infection was significantly higher than those without HP infection and there was significant association between severity of HP infection and hs-CRP level.…”
Section: Discussionsupporting
confidence: 90%
“…We also found that serum hs-CRP levels have been affected by the severity of acute or chronic inflammation. Furthermore, Raut et al 6 evaluated 80 patients and found that patients with chronic gastritis and HP infection was higher hs-CRP levels than chronic gastritis patients without HP. Similarly in a study of 239 patients with chronic gastritis, Rahmani et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The possible mechanism was reported as decreased methylation due to vitamin and folate deficiency, characteristic of chronic gastritis. The resultant increase in plasma homocysteine levels produces toxic effects in endothelial cells leading to the development of coronary artery disease [24]. However, this causal relationship was not supported by earlier clinical investigations.…”
Section: Helicobacter Pylorimentioning
confidence: 94%